Fuzzy logic controlled solar module for driving three-phase induction motor - Chan, Sooi Tat (2015)
Renewable Energy such as solar modules to generate electricity are getting serious in modern life due to high consumption of electricity generation for applications such as three-phase induction motor. The three-phase induction motor been used widely for industrial applications and the speed to be controlled by variable frequency using power electronics. Solar modules used to generate electricity to supply the three phase induction motor but photovoltaic output is uncertain and complexity. The Fuzzy Logic controller is one of controllers that can handle non-linear system and maximum power of solar module. Fuzzy logic controller to be used for Maximum Power Point Tracking (MPPT) in the non-linear system with fuzzy rules to control Pulse-Width Modulation (PWM) for switching Metal Oxide Semiconductor Fast Emitted Transistor (MOSFET). DC boost converter used to boost up photovoltaic voltage to desired output for supply voltage source inverter which controlled by three-phase PWM generated by microcontroller. IGBT switched Voltage source inverter produced alternating current (AC) voltage from direct current (DC) source to control speed of three-phase induction motor from boost converter output.